On the Lived‐Experience and Dynamics of Health and Illness: Phenomenological Complexity and Learning Organizations - Stanley, Darren (Paideusis, 2007)
Many contemporary theories of “complex” dynamical phenomena have been used to explain and understand a wide range of matters pertaining to the health of learning organizations; however, a more sensitive approach is required which also takes into account the lived-experience of health where the experiencing subject is also a part of an epistemological framework which Letiche1 describes as “phenomenal complexity theory.” To be sure, there is a need for a complexity-related framework which also studies human consciousness by attending to the structures of lived-experience—in the case of this paper, the lived-structures of health. To this end, this paper examines: the notion of “health” through a circulation of lived-experience; the concept of dynamical systems in an emerging framework for studying healthy learning organizations.